Effect of Early Electroacupuncture Combined with Enhanced Recovery after Surgery (ERAS) on Pain Perception and Dysfunction in Patients after Total Knee Arthroplasty (TKA). (9th May 2022) - Zhang, Tian; Liu, Hongju; Li, Hui; He, Sha; Xiao, Li; Qin, Ting; Xu, Wei long
Abstract : Objective . A retrospective case-control study was performed to observe the effect and clinical significance of early electroacupuncture combined with enhanced recovery after surgery (ERAS) on pain perception and dysfunction after total knee arthroplasty (TKA). Methods . About 100 patients who diagnosed with TKA from February 2019 to April 2021 were enrolled in our hospital. The patients were arbitrarily assigned into control group and study group. The former group was cured with electroacupuncture in the early stage, and the latter group was intervened on the basis of early electroacupuncture combined with the concept of ERAS. The curative effect, the time of getting out of bed for the first time after operation, the time of postoperative rehabilitation, postoperative rehabilitation cost, pain score and knee joint function score, range of motion (ROM) of knee joint, low shear of whole blood viscosity, plasma viscosity, fibrinogen level, and postoperative complications were compared. Results . There exhibited no statistical difference in clinical data. In terms of the treatment effects, there were 27 cases of markedly effective, 22 cases of effective, and 1 case of ineffective in the study group, and the total effective rate was 98.00%; in the control group, 15 cases were markedly effective, 28 cases were effective, and 13 cases were ineffective, and the total effective rate was 86.00%. Compared to the control group, the total effective rate of the study group was higher (P < 0.05 ). And the first time to get out of bed and the postoperative rehabilitation time in the study group were lower. Compared to the control group (10113.42 ± 524.83) yuan, the postoperative rehabilitation cost in the study group (12401.71 ± 530.77) yuan was higher. In terms of the scores of VAS and HSS, there exhibited no remarkable difference before treatment (P > 0.05 ). After treatment, the VAS score lessened and the HSS score augmented the study group VAS score (1.76 ± 0.28); the score in the control group was lower compared to the control group (3.45 ± 0.36), and HSS scoring (83.48 ± 11.23) points higher compared to the control group (65.82 ± 10.44) points (P < 0.05 ). The ROM of knee joint augmented successively at the 1st, 2nd, 4th, and 8th week after treatment comparison between groups, the ROM of the knee joint in the study group at the 1st, 2nd, 4th, and 8th week was (49.47 ± 3.60)°, (64.38 ± 5.32)°, (86.93 ± 6.72)°, and (104.20 ± 9.11)°, is higher compared to the control group (46.53 ± 3.41)°, (61.52 ± 5.20)°, (78.42 ± 6.45)°, and (98.77 ± 8.67)° (P < 0.05 ). One day after operation, there exhibited no remarkable difference in whole blood viscosity low shear, plasma viscosity, and fibrinogen level (P > 0.05 ). However, there exhibited no remarkable difference in plasma viscosity and fibrinogen level at 1 day and 7 days after operation (P > 0.05 ). Seven days after operation, the whole blood viscosity, plasma viscosity, and fibrinogen in the study group were lower (P < 0.05 ). The probability of postoperative complications was compared. In the study group, there were 2 cases of limb swelling and pain, 1 case of joint stiffness, and no swelling and pain complicated with deep venous thrombosis, and the total incidence was 6.00%. In the control group, there were 5 cases of limb swelling and pain, 3 cases of joint stiffness, and 3 cases of swelling and pain complicated with deep venous thrombosis, with a total incidence of 22.00%. The incidence of adverse reactions in the study group was lower (χ 2  = 5.317 P < 0.05 ). Conclusion . Early electroacupuncture combined with ERAS is of positive significance to the patients after TKA, which can reduce the pain, enhance the function of the knee joint, and promote the ROM of the knee joint, and can effectively shorten the first time out of bed and postoperative rehabilitation time and reduce whole blood viscosity low shear, plasma viscosity, and fibrinogen level, but the overall rehabilitation cost is high, and clinical application should be combined with the actual situation of patients.